2016
DOI: 10.3390/rs8050390
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of HY-2A Scatterometer Wind Vectors Using Data from Buoys, ERA-Interim and ASCAT during 2012–2014

Abstract: Abstract:The first Chinese operational Ku-band scatterometer on board Haiyang-2A (HY-2A), launched in August 2011, is designed for monitoring the global ocean surface wind. This study estimates the quality of the near-real-time (NRT) retrieval wind speed and wind direction from the HY-2A scatterometer for 36 months from 2012 to 2014. We employed three types of sea-surface wind data from oceanic moored buoys operated by the National Data Buoy Center (NDBC) and the Tropical Atmospheric Ocean project (TAO), the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…Therefore, dealing with rain contaminated data is one of the difficulties in scatterometer wind retrieval. It is especially important for scatterometer data usage under rainy conditions to study HSCAT wind field variations at different rainfall rates [20].…”
Section: The Rain Impact On Hscat Wind Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, dealing with rain contaminated data is one of the difficulties in scatterometer wind retrieval. It is especially important for scatterometer data usage under rainy conditions to study HSCAT wind field variations at different rainfall rates [20].…”
Section: The Rain Impact On Hscat Wind Productsmentioning
confidence: 99%
“…Xing et al (2016) also validated HSCAT wind products by using NDBC buoys, TAO, the European Centre for Medium Range Weather Forecasting (ECMWF) reanalysis data (ERA-Interim), and ASCAT data during 2012-2014. They found that rain has a significant effect on overestimating HSCAT wind speed at low and moderate wind speeds [20]. Bhaskar et al (2016) generated and evaluated two-day OSCAT wind fields with tropical Indian Ocean buoys and ASCAT data [21].…”
mentioning
confidence: 99%
“…A few studies have been conducted on the quality assessment of HY-2A data. Xing et al [13] compared the data of HY-2A with the data of the NDBC (National Data Buoy Center) of the National Oceanic and Atmospheric Administration (NOAA), the data of the European Centre for Medium Range Weather Forecasting (ECMWF), and the data of the advanced scatterometer (ASCAT). The result shows that the quality performances of the HY-2A near-real-time wind vector data (especially the wind speeds) were satisfactory throughout the service period.…”
Section: Range Of the Significantmentioning
confidence: 99%
“…Wave Height (m) 13.58/5.25 ≤2 ≤8 0. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] As the other microwave sensor, the scatterometer mounted on HY-2A is used to provide observations of vector wind at the sea surface.…”
Section: Range Of the Significantmentioning
confidence: 99%
See 1 more Smart Citation